Key Drivers for Building School Effectiveness: An Analysis of Leadership and Organizational Behaviour Dynamics - Yumarni, Asmara; Kristiawan, Muhammad; Anwar, Khairul; Firmansyah, Leppe; Nugraha, Hilman; Wati, Retno Ambar (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
This study aims to investigate the impact of servant leadership, organizational commitment, social skills, work autonomy, organizational behavior, and organizational legitimacy on organizational effectiveness. Employing a quantitative approach, data were collected from 78 teachers at SMPS 1 Medan via a 5-point Likert scale questionnaire and analyzed using Pearson correlation and regression analyses. The findings indicate that servant leadership (r=0.566, p<0.001), organizational commitment (r=0.676, p<0.001), social skills (B=0.196, p<0.05), work autonomy (r=0.870, p<0.001), organizational behavior (r=0.652, p<0.001), and organizational legitimacy (B=0.255, p<0.001) all have a statistically significant positive effect on organizational effectiveness. The primary novelty lies in the empirical validation of these relationships within the madrasah setting, highlighting the exceptionally strong influence of work autonomy and the dominant contribution of organizational legitimacy (67.9%). These results extend existing organizational theories by providing contextual empirical evidence and offer practical implications for school administrators and policymakers to strategically enhance organizational effectiveness through fostering social skills and, critically, securing organizational legitimacy.